Insider Trading sebagai Bentuk Kejahatan Ekonomi di Pasar Modal Indonesia (Studi Kasus PT Danareksa Sekuritas) - Syuryadi, Paksi Aan; Tamza, Fristia Berdian; Fardiansyah, Ahmad Irzal (ARBITER: Jurnal Ilmiah Magister Hukum, 2025)
The enforcement of insider trading laws in Indonesia is currently impeded by structural deficiencies within Law Number 8 of 1995 concerning Capital Markets (UUPM), particularly regarding the inherent limitations of the Fiduciary Duty Theory in addressing crimes committed by institutional intermediaries. This study aims to critique these doctrinal limitations and analyze the urgency of adopting the Misappropriation Theory as an alternative dogmatic foundation. Employing normative legal research (doctrinal research) with statute, conceptual, and case approaches, the study reveals that the current legal construction fails to encompass institutional insiders as exemplified by the PT Danareksa Sekuritas case. Consequently, law enforcement is frequently reduced to mere administrative sanctions due to complex evidentiary hurdles. This article concludes that the Fiduciary Duty Theory is no longer sufficient for modern capital market complexities. Therefore, the adoption of the Misappropriation Theory through a progressive interpretation of Article 97 of the UUPM is recommended to bridge the legal gap and ensure rigorous criminal prosecution.